Overuse injuries of the lower extremity in runners - Rolf, C. (Scandinavian Journal of Medicine & Science in Sports, 1995)
The purpose of this article is to review the literature on overuse injuries of the lower extremity in runners and to discuss briefly today's knowledge concerning etiology, diagnosis and treatment. Running is a natural entity in many sports and a majority of runners will sustain one or more overuse injuries throughout the career, in most cases affecting the lower extremity. A runner may be regarded as an athlete who regularly runs as the predominant physical activity. From that point, we should subdivide the definition "runner" considering the character of different sports or recreational activities performed. Overuse injuries are often described merely from symptoms, including several different etiological and pathoanatomic correlates covering a variety of ailments. The clinical approach should be focused on a thorough history and physical examination. Analysis of possible injury mechanisms, correction of associated extrinsic and intrinsic factors and advice on alternative training should be given. A knowledge of specific demands from the type of running performed is necessary to evaluate the symptoms presented. Overuse etiology has to be considered multifactorial with a yet unsolved exact pathophysiology needing further research. The definition of a "runner", of "running" and of "overuse injury" should be established and agreed upon. This review attempts to draw attention to the huge multidisciplinary work that has to be done to better understand the mechanisms causing an overuse injury in a runner and to define diagnoses on a scientific base, whether or not excentric or intrinsic factors predispose or trigger.